1999
DOI: 10.1364/ao.38.005181
|View full text |Cite
|
Sign up to set email alerts
|

Resonant waveguide–grating switching device with nonlinear optical material

Abstract: The design and analysis of a dielectric guided-mode resonance filter (GMRF) utilizing a nonlinear material for the waveguide is presented. Small changes to the parameters of a GMRF have a large impact on its resonance. A nonlinear material can provide a small change in the refractive index of the waveguide, altering the resonance of the device and resulting in modulation of the transmitted and reflected output of the filter. Numerical results show that nonlinear switching from 100% transmission to 100% reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Also, we are employing linear modeling codes, such as Rigorous Coupled Wave Analysis to predict the optical response as a function of waveguide index. Figure 3 shows the cross-section of an RSG design [3] utilized in the analysis on an active component around an incident, visible wavelength of 638.6 nm. The predicted transmitted and reflected resonances are shown in Figure 4 for a normally incident beam with TE polarization, as a function of input wavelength.…”
Section: Active Resonant Subwavelength Grating Design Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we are employing linear modeling codes, such as Rigorous Coupled Wave Analysis to predict the optical response as a function of waveguide index. Figure 3 shows the cross-section of an RSG design [3] utilized in the analysis on an active component around an incident, visible wavelength of 638.6 nm. The predicted transmitted and reflected resonances are shown in Figure 4 for a normally incident beam with TE polarization, as a function of input wavelength.…”
Section: Active Resonant Subwavelength Grating Design Considerationsmentioning
confidence: 99%
“…To avoid the absorption evident in Figure 14, a dual-layer grating can distance the lossy ITO from the high electric fields present in the guiding layer. The lower layer of the grating may be either the low-index SiO 2 , or the high-index BaTiO 3 . Figure 15 shows the results of the numerical simulation for the SiO 2 case.…”
Section: Active Rsg Materials Survey and Simulationsmentioning
confidence: 99%
“…Magnusson and Wang firstly suggested that GMR filters can be used as tunable optical filters or as low-power optical switching devices 7 . Then theoretical studies 8 and other types of tunable GMR devices 2,3,9 have been demonstrated [10][11][12] . Some studies involve the E-O effect in liquid crystals to tune the resonance wavelength in dielectrics 13,14 or metallic (plasmonic) 15 GMR filters.…”
Section: Introductionmentioning
confidence: 99%
“…Research in this field has the potential of producing a new class of passive elements called resonant waveguide gratings with a large number of applications. A few of these possible uses include static and tunable spectral filters with arbitrarily narrow, controlable linewidths, optical switches and modulators, polarizers, couplers, and many other applications [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%